Novel inert titanium anode and preparation method thereof
By combining the electrodeposition and spraying process, a layered structure coating containing ruthenium, iridium and tin oxides was generated by thermal decomposition method, which solved the problem that the coated titanium anode was prone to fall off in acidic medium, and achieved the effect of good electrochemical performance and long service life.
Patent Information
- Application Number
- CN202510093788.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The existing coated titanium anode is prone to fall off in acidic media, resulting in electrode failure, short life and low economic benefits.
By combining electrodeposition with spraying technology, a layered structure coating containing ruthenium, iridium and tin oxides is generated in situ by thermal decomposition, forming a substituted solid solution of multi-oxides, increasing oxygen deficiency, thereby improving the enhanced life and catalytic activity of the coating.
The electrochemical performance and long service life of the coated titanium anode are achieved, especially under acidic and high current density, and its catalytic stability is excellent.
Smart Images

Figure CN119859823A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemical technology, and in particular relates to a novel inert titanium anode and a preparation method thereof. Background Art
[0002] The coated titanium anode is also called DSA or MMOA. It is a new type of high-efficiency and energy-saving electrode. It is mainly composed of a titanium metal substrate and an active coating on its surface. Ru and Ir oxides have good corrosion resistance, conductivity and good catalytic activity, and are the main components of titanium anode coating. SnO2 is an N-type semiconductor material, and during the heat treatment process, cation vacancies appear to generate free electrons to enhance conductivity. In addition, Ru, Ir, and Sn all have tetrahedral structures and roughly equal atomic sizes, which are easy to form substitutional solid solutions of multi-electrons, resulting in more oxygen vacancies and increased catalytic activity. Domestic and foreign scholars have done a lot of research and improvement work on ruthenium and iridium coated titanium anodes, some of which have been successfully applied in the chlor-alkali industry, electrolysis and electroplating processes, but there is still a problem that the anode coating is easy to fall off in acidic media, resulting in electrode failure, short life, and low economic benefits.
[0003] Thermal decomposition is the main method for industrial production of coated titanium anodes. This process has the advantages of mature technology, low cost and stable products. At present, the stability of the coating structure is mainly solved by optimizing the coating composition, structure and preparation process. The patent with publication number CN118461064A discloses a method for preparing a titanium anode with iridium, ruthenium, tin and titanium coatings. The metal salt solution is mixed and then coated on a titanium substrate for heat treatment to prepare a coated anode. However, the strength of the titanium anode coating prepared by this process is still insufficient, the strengthening life is not long enough, and it is difficult to meet the catalytic stability in high current density and acidic solution. Summary of the invention
[0004] In order to solve the above technical problems and further improve the stability and life of the coated titanium anode, the present invention proposes a new inert titanium anode and a preparation method thereof, which combines electrodeposition with spraying process and adopts thermal decomposition method to in-situ generate a layered structure coating containing ruthenium, iridium and tin oxides.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention:
[0007] A novel inert titanium anode comprises a titanium substrate and an anode coating, wherein the anode coating is loaded on the surface of the titanium substrate and is a layered structure containing three metal oxides, wherein the inner layer of the anode coating is ruthenium oxide (RuO2), the middle layer is iridium oxide (IrO2), and the outer layer is tin oxide (SnO2).
[0008] Furthermore, the mass ratio of ruthenium oxide, iridium oxide and tin oxide in the anode coating is (0.6-1.2):(0.3-0.7):(0.01-0.05).
[0009] The second technical solution of the present invention:
[0010] A preparation method of the novel inert titanium anode comprises the following steps: using an electrodeposition method to deposit ruthenium and iridium on the surface of a titanium plate in sequence, then using a spraying process to spray a tin-containing solution on the surface, and finally using a thermal decomposition method to in-situ generate a layered structure coating containing ruthenium, iridium and tin oxides on the surface of the titanium plate to obtain the novel inert titanium anode.
[0011] Furthermore, the preparation method of the novel inert titanium anode specifically comprises the following steps:
[0012] (1) A titanium substrate is obtained by pretreatment, the titanium substrate is used as a cathode, a metal platinum sheet is used as an anode, and the titanium substrate is immersed in a ruthenium-containing solution, and ruthenium is electrodeposited on the surface of the titanium plate by an electrodeposition method to prepare an electrode A;
[0013] (2) using the electrode A obtained in step (1) as a cathode and a metal platinum sheet as an anode, immersing the electrodes in an iridium-containing solution, and electrodepositing iridium on the surface of the electrode A by an electrodeposition method to prepare an electrode B;
[0014] (3) Spraying a tin-containing solution on the surface of the electrode B obtained in step (2), followed by drying and heat treatment to obtain the novel inert titanium anode.
[0015] Furthermore, in step (1), the ruthenium-containing solution comprises RuCl3 at a concentration of 10-15 g / L and NH2SO3H at a pH of 1-2; and / or
[0016] The solution temperature of the electrodeposition method is 45-50°C, and the current density is 1.0-1.5A / dm 2 , the deposition time is 1-2h.
[0017] Furthermore, the ruthenium-containing solution is obtained by dissolving RuCl3 in deionized water, then adding NH2SO3H, and ultrasonically treating at 20-30kHz for 10 minutes.
[0018] Furthermore, in step (2), the iridium-containing solution comprises H2IrCl5·6H2O at a concentration of 10-15 g / L and CH3COOH at a pH of 4-5; and / or
[0019] The solution temperature of the electrodeposition method is 85°C and the current density is 1.0-2.0A / dm 2 , the deposition time is 1-2h.
[0020] Furthermore, the electrodeposition method is performed in an air atmosphere.
[0021] Furthermore, the iridium-containing solution is obtained by dissolving H2IrCl5·6H2O in deionized water, then adding CH3COOH, and ultrasonically treating at 20-30 kHz for 10 minutes.
[0022] Furthermore, in step (3), the tin-containing solution is a SnCl4 solution with a concentration of 20 g / L; and / or
[0023] The drying is infrared drying; and / or
[0024] The heat treatment temperature is 450-550° C. and the time is 1 hour.
[0025] Furthermore, in step (3), the spraying is carried out using an electric spraying device, and the caliber of the spray gun is 0.5-1.5 mm.
[0026] Furthermore, in step (3), the tin-containing solution is sprayed multiple times, and the spraying of the tin-containing solution-infrared heat drying-heat treatment process is repeated. After spraying the tin-containing solution, infrared heat drying treatment is quickly performed, and then it is transferred to an electric furnace for heat treatment at 450-550° C. for 10 minutes, and spraying is continued after cooling.
[0027] Furthermore, the tin-containing solution is obtained by dissolving SnCl4 in an organic solvent and subjecting the solution to ultrasonic treatment at 20-30 kHz for 10 minutes, wherein the organic solvent used is anhydrous ethanol and ethylene glycol in a volume ratio of 1:1.
[0028] Furthermore, in step (1), the titanium plate pretreatment specifically includes the following steps:
[0029] Use an electric grinder or coarse sandpaper to preliminarily grind the titanium plate to remove surface impurities;
[0030] The polished titanium plate is immersed in an alkaline solution, and then immersed in an oxalic acid solution after washing, and acid-etched for 2-3 hours under a slightly boiling state, and then washed, and then immersed in anhydrous ethanol for ultrasonic treatment, and washed again to obtain a titanium matrix.
[0031] Furthermore, during the titanium plate pretreatment process, the alkaline solution is a sodium hydroxide solution or a sodium carbonate solution with a concentration of 5 wt%; and / or
[0032] The concentration of the oxalic acid solution is 10-15 wt %.
[0033] Furthermore, during the pretreatment of the titanium plate, the ultrasonic treatment time is 10-15 minutes and the ultrasonic frequency is 20-30 kHz.
[0034] Compared with the prior art, the present invention has the following advantages and technical effects:
[0035] The invention provides a novel inert titanium anode and a preparation method thereof. The prepared novel inert titanium anode (ruthenium, iridium, and tin coating) has the characteristics of good electrochemical performance and long service life. Ruthenium and iridium metals are deposited in sequence on the electrode surface by an electrodeposition method, which has the advantages of strong structure and good uniformity. Since Ru, Ir, and Sn have the same structure and roughly equal atomic sizes, oxides generated in situ are treated by a thermal decomposition process, so that substitutional solid solutions of multi-element oxides can be formed therebetween, increasing oxygen vacancies in the coating material, thereby increasing the enhanced service life and catalytic activity of the coating, especially under acidic conditions and high current density, the catalytic stability thereof is excellent. In addition, the use of electrospraying can maintain the uniformity and production efficiency of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0037] Figure 1 The schematic diagram and scanning electron microscope image of the structure of the novel inert titanium anode and anode coating prepared in Example 1 of the present invention;
[0038] Figure 2 This is a comparison chart of cyclic voltammetry tests of titanium anodes prepared in Examples 1-6 and Comparative Examples 1-4;
[0039] Figure 3 These are the experimental results of the enhanced life test of the titanium anodes prepared in Examples 1-6 and Comparative Examples 1-4. DETAILED DESCRIPTION
[0040] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0041] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0042] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0043] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0044] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0045] An embodiment of the present invention proposes a novel inert titanium anode, comprising a titanium substrate and an anode coating, wherein the anode coating is loaded on the surface of the titanium substrate, the anode coating is a layered structure containing three metal oxides, the inner layer of the anode coating is ruthenium oxide (RuO2), the middle layer is iridium oxide (IrO2), and the outer layer is tin oxide (SnO2).
[0046] In a preferred embodiment of the present invention, the mass ratio of ruthenium oxide, iridium oxide and tin oxide in the anode coating is (0.6-1.2):(0.3-0.7):(0.01-0.05).
[0047] The embodiment of the present invention also proposes a method for preparing the novel inert titanium anode, which uses an electrodeposition method to deposit ruthenium and iridium on the surface of a titanium plate in sequence, then uses a spraying process to spray a tin-containing solution on the surface, and finally uses a thermal decomposition method to in-situ generate a layered structure coating containing ruthenium, iridium, and tin oxides on the surface of the titanium plate to obtain the novel inert titanium anode, which specifically includes the following steps:
[0048] (1) A titanium substrate is obtained by pretreatment, the titanium substrate is used as a cathode, a metal platinum sheet is used as an anode, and the titanium substrate is immersed in a ruthenium-containing solution to electrodeposit ruthenium on the surface of the titanium plate to prepare an electrode A;
[0049] (2) using the electrode A obtained in step (1) as a cathode and a metal platinum sheet as an anode, immersing the electrodes in an iridium-containing solution, and electrodepositing iridium on the surface of the electrode A to prepare an electrode B;
[0050] (3) Spraying a tin-containing solution on the surface of the electrode B obtained in step (2), followed by drying and heat treatment to obtain the novel inert titanium anode.
[0051] The present invention uses electrodeposition to deposit ruthenium and iridium metals in sequence on the electrode surface, which has the advantages of strong structure and good uniformity. Since Ru, Ir and Sn have the same structure and roughly equal atomic sizes, oxides generated in situ by thermal decomposition process can form substitutional solid solutions of multi-element oxides, thereby increasing oxygen vacancies in the coating material and increasing the catalytic activity of the coating. Further, the use of electrospraying can maintain the uniformity and production efficiency of the coating.
[0052] In step (1) of the preferred embodiment of the present invention, the ruthenium-containing solution comprises RuCl3 at a concentration of 10-15 g / L and NH2SO3H at a pH of 1-2; and / or
[0053] The solution temperature of the electrodeposition is 45-50°C and the current density is 1.0-1.5A / dm 2 , duration 1-2 hours; and / or
[0054] The ruthenium-containing solution is obtained by dissolving RuCl3 in deionized water, then adding NH2SO3H, and ultrasonically treating at 20-30kHz for 10 minutes.
[0055] In step (2) of the preferred embodiment of the present invention, the iridium-containing solution comprises H2IrCl5·6H2O at a concentration of 10-15 g / L and CH3COOH at a concentration of 0.01-0.02 mol / L, and a pH of 4-5; and / or
[0056] The electrodeposition solution temperature is 85°C and the current density is 1.0-2.0A / dm 2 , duration 1-2 hours; and / or
[0057] The iridium-containing solution is obtained by dissolving H2IrCl5·6H2O in deionized water, then adding CH3COOH, and subjecting the solution to ultrasonic treatment at 20-30 kHz for 10 minutes.
[0058] In a preferred embodiment of the present invention, the electrodeposition method is performed in an air atmosphere.
[0059] In step (3) of the preferred embodiment of the present invention, the tin-containing solution is a SnCl4 solution with a concentration of 20 g / L; and / or
[0060] The drying is infrared drying; and / or
[0061] The heat treatment temperature is 450-550°C and the time is 1 hour; and / or
[0062] The tin-containing solution is obtained by dissolving SnCl4 in an organic solvent and subjecting it to ultrasonic treatment at 20-30 kHz for 10 minutes, wherein the solvent used is anhydrous ethanol and ethylene glycol in a volume ratio of 1:1.
[0063] In step (3) of the preferred embodiment of the present invention, the spraying is carried out using an electrospraying device, the caliber of the spray gun is 0.5-1.5 mm, preferably 0.9 mm, and the flow rate is 300 mL / min.
[0064] In step (3) of the preferred embodiment of the present invention, the tin-containing solution is sprayed multiple times, and the spraying of the tin-containing solution-infrared heat drying-heat treatment process is repeated. The sprayed tin-containing solution is quickly subjected to infrared heat drying treatment, and then transferred to an electric furnace for heat treatment at 450-550° C. for 10 minutes, and then spraying is continued after cooling.
[0065] In step (1) of the preferred embodiment of the present invention, the titanium plate pretreatment specifically includes the following steps:
[0066] Use an electric grinder or coarse sandpaper to preliminarily grind the titanium plate to remove surface impurities;
[0067] The polished titanium plate is immersed in an alkaline solution, and then immersed in an oxalic acid solution after washing, and acid-etched for 2-3 hours under a slightly boiling state, and then washed, and then immersed in anhydrous ethanol for ultrasonic treatment, and washed again to obtain a titanium matrix, wherein the alkaline solution is a sodium hydroxide solution or a sodium carbonate solution with a concentration of 5wt%; and / or
[0068] The concentration of the oxalic acid solution is 10-15wt%; and / or
[0069] The ultrasonic treatment time is 10-15 min, and the ultrasonic frequency is 20-30 kHz.
[0070] The raw materials used in the embodiments of the present invention are all commercially available.
[0071] The technical solution of the present invention is further illustrated by the following embodiments.
[0072] Example 1
[0073] A method for preparing a novel inert titanium anode comprises the following steps:
[0074] (1) The titanium plate was preliminarily polished with an electric grinder (3000 r / min, grinding wheel diameter 125 mm, sandpaper 150 mesh) to remove surface impurities, then immersed in a 5 wt% sodium hydroxide solution at 60°C for 1 h, rinsed with deionized water, immersed in a 10 wt% oxalic acid solution, acid-etched for 2 h at a slightly boiling state, rinsed with deionized water, immersed in anhydrous ethanol, ultrasonically treated at 30 kHz for 10 min, and then washed with deionized water to obtain a titanium substrate with a rough and clean surface;
[0075] (2) The titanium substrate obtained in step (1) is used as the cathode and the metal platinum sheet is used as the anode, and is immersed in a ruthenium-containing solution (containing 10 g / L RuCl3, 10 g / L NH2SO3H, pH 2), and ruthenium is electrodeposited on the surface of the titanium plate by electrodeposition. The solution temperature of the electrodeposition method is 50°C and the current density is 1.0 A / dm 2 , the deposition time is 1h, and electrode A is prepared;
[0076] (3) The electrode A obtained in step (2) is used as a cathode and a metal platinum sheet is used as an anode, and is immersed in an iridium-containing solution (containing 15 g / L H2IrCl5·6H2O and 0.015 mol / L CH3COOH, pH 5), and iridium is deposited on the surface of the electrode A by an electrodeposition method. The solution temperature of the electrodeposition method is 85° C. and the current density is 1.5 A / dm 2 , the deposition time is 1h, and electrode B is prepared;
[0077] (4) The surface of the electrode B obtained in step (3) was sprayed with 20 g / L SnCl4 solution (the spray gun diameter was 0.9 mm and the flow rate was 300 mL / min), and then dried by infrared irradiation for 15 min. The electrode was then placed in an electric furnace for heat treatment at 500°C for 10 min. The above operation was repeated 5 times, with the last heat treatment at 500°C for 1 h. After cooling, a new inert titanium anode was obtained.
[0078] The structural schematic diagram and scanning electron microscope image of the novel inert titanium anode and anode coating prepared in Example 1 of the present invention are shown in Figure 1 It can be seen that the new inert titanium anode includes a titanium substrate and an anode coating. The total length of the new inert titanium anode plate is 158mm, the effective working length is 138mm, and the width is 75mm (the length and width only represent the size of the titanium anode plate prepared and tested. Only the mesh part has a coating on the surface, which is the effective working area). The coating is mainly composed of a three-layer structure of SnO2 layer, IrO2 layer and RuO2 layer, and the layers are firmly bonded. In addition, according to the scanning electron microscope image, it can be seen that the surface of the anode coating is uniformly porous. This structure is conducive to increasing the effective area of the coating and improving the electrochemical performance of the electrode.
[0079] Example 2
[0080] A method for preparing a novel inert titanium anode is the same as that of Example 1, except that the electrodeposition time in step (2) is 2 hours.
[0081] Example 3
[0082] A method for preparing a novel inert titanium anode is the same as that of Example 1, except that the electrodeposition time in step (3) is 2 hours.
[0083] Example 4
[0084] A method for preparing a novel inert titanium anode is the same as that of Example 1, except that the electrodeposition time in step (2) is 2 hours, and the electrodeposition time in step (3) is 2 hours.
[0085] Example 5
[0086] (1) The titanium plate was preliminarily polished with an electric grinder to remove surface impurities, then immersed in a 5 wt % sodium hydroxide solution at 60° C. for 1 h, rinsed with deionized water, immersed in a 15 wt % oxalic acid solution, and acid-etched for 3 h at a slightly boiling state. After being rinsed with deionized water, the titanium plate was immersed in anhydrous ethanol, ultrasonically treated at 30 kHz for 10 min, and then washed with deionized water to obtain a titanium substrate with a rough and clean surface;
[0087] (2) The titanium substrate obtained in step (1) is used as the cathode and the metal platinum sheet is used as the anode, and is immersed in a ruthenium-containing solution (containing 15 g / L RuCl3, 10 g / L NH2SO3H, pH 1), and ruthenium is electrodeposited on the surface of the titanium plate by electrodeposition. The solution temperature of the electrodeposition method is 50°C and the current density is 1.5 A / dm 2 , the deposition time is 1h, and electrode A is prepared;
[0088] (3) The electrode A obtained in step (2) is used as a cathode and a metal platinum sheet is used as an anode, and is immersed in an iridium-containing solution (containing 15 g / L H2IrCl5·6H2O and 0.01 mol / L CH3COOH, pH 5), and iridium is deposited on the surface of the electrode A by electrodeposition. The solution temperature of the electrodeposition is 85°C and the current density is 2.0 A / dm 2 , the deposition time is 1h, and electrode B is prepared;
[0089] (4) The surface of the electrode B obtained in step (3) was sprayed with 20 g / L SnCl4 solution (the spray gun diameter was 0.9 mm and the flow rate was 300 mL / min), and then dried by infrared irradiation for 15 min. Then, the electrode was placed in an electric furnace for heat treatment at 550°C for 10 min. The above operation was repeated 5 times, and the last heat treatment was performed at 500°C for 1 h. After cooling, a new inert titanium anode was obtained.
[0090] Example 6
[0091] (1) The titanium plate was preliminarily polished with coarse sandpaper (specification: less than 400 mesh) to remove surface impurities, then immersed in a 5wt% sodium carbonate solution at 60°C for 1 hour, rinsed with deionized water, immersed in a 10wt% oxalic acid solution, acid-etched for 2 hours under a slightly boiling state, rinsed with deionized water, immersed in anhydrous ethanol, ultrasonically treated at 20kHz for 15 minutes, and then washed with deionized water to obtain a titanium substrate with a rough and clean surface;
[0092] (2) The titanium substrate obtained in step (1) is used as the cathode and the metal platinum sheet is used as the anode, and is immersed in a ruthenium-containing solution (containing 10 g / L RuCl3, 10 g / L NH2SO3H, pH 2), and ruthenium is electrodeposited on the surface of the titanium plate by electrodeposition. The solution temperature of the electrodeposition method is 45°C and the current density is 1.0 A / dm 2 , the deposition time is 2h, and electrode A is prepared;
[0093] (3) The electrode A obtained in step (2) is used as a cathode and a metal platinum sheet is used as an anode, and is immersed in an iridium-containing solution (containing 10 g / L H2IrCl5·6H2O and 0.02 mol / L CH3COOH, pH 4), and iridium is deposited on the surface of the electrode A by an electrodeposition method. The solution temperature of the electrodeposition method is 85° C. and the current density is 1.0 A / dm 2 , the deposition time is 2h, and electrode B is prepared;
[0094] (4) The surface of the electrode B obtained in step (3) was sprayed with 20 g / L SnCl4 solution (the spray gun diameter was 0.9 mm and the flow rate was 300 mL / min), and then dried by infrared irradiation for 15 min. Then, the electrode was placed in an electric furnace for heat treatment at 450°C for 10 min. The above operation was repeated 5 times, and the last heat treatment was performed at 500°C for 1 h. After cooling, a new inert titanium anode was obtained.
[0095] Comparative Example 1
[0096] The titanium substrate with a rough and clean surface is prepared by the same method as step (1) in Example 1.
[0097] Comparative Example 2
[0098] Same as Example 1, except that in step (2), the solution temperature of the electrodeposition method is 80°C and the current density is 2A / dm 2 , the deposition time is 0.5h.
[0099] Comparative Example 3
[0100] Same as Example 1, except that in step (3), the solution temperature of the electrodeposition method is 60°C and the current density is 0.5A / dm 2 , the deposition time is 0.5h.
[0101] Comparative Example 4
[0102] The same as Example 1, except that in step (4), 50 g / L SnCl4 solution is sprayed on the surface of the electrode B obtained in step (3), and then placed in an electric furnace for heat treatment at 500°C for 1 h, and then cooled to obtain an inert titanium anode.
[0103] The proportions of various elements in the anode coatings of the novel inert titanium anodes prepared in the above Examples 1-6 and Comparative Examples 1-4 were measured, and compared with the titanium substrate of Comparative Example 1. The results are shown in Table 1.
[0104] Table 1 Proportion of each element in the anode coating in Examples 1-6 and Comparative Examples 1-4
[0105] Element content / g Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 <![CDATA[RuO2]]> 0.665 1.200 0.662 1.196 0.788 0.814 0 0.682 0.662 0.663 <![CDATA[IrO2]]> 0.332 0.340 0.660 0.663 0.462 0.462 0 0.331 0.341 0.331 <![CDATA[SnO2]]> 0.02 0.021 0.019 0.042 0.027 0.021 0 0.022 0.019 0.02
[0106] Performance Testing
[0107] Cyclic voltammetry curve test and enhanced life test were performed on the titanium anodes prepared in Examples 1-6 and Comparative Examples 1-4.
[0108] The test conditions of the cyclic voltammetry curve are: potential range -0.7V-0.7V, scan rate 10mV / s.
[0109] The enhanced life test conditions are: using a DC regulated power supply at room temperature, the anode is a coated titanium anode, the cathode is a metal titanium mesh, and the current density is 2A / cm 2 , the inter-electrode distance is 2 cm, the electrolyte is 1 mol / L H2SO4 solution, and the cell voltage rises to 10 V, indicating electrode failure.
[0110] The comparison diagram of cyclic voltammetry test of titanium anode prepared in Example 1-6 and Comparative Example 1-4 is shown in Figure 2 The size of the image area in the cyclic voltammetry test diagram can be clearly judged. The area of the graphic indicates that the catalytic performance of the plate surface is good. Combined with Table 1 and Figure 2It can be seen that the composition of the effective substances of the anode coating under different conditions is significantly different. The catalytic activity of the coated titanium anode is significantly higher than that of the uncoated anode. The uncoated anode is easy to form a dense oxide film on the surface in an acidic solution, which significantly reduces the electrode conductivity and catalytic performance, and then causes the anode voltage to rise sharply and fail, and the life is the shortest. The cyclic voltammetry curves of Examples 1 to 6 all have a large area, among which the area surrounded by the cyclic voltammetry curve corresponding to Example 4 is the largest, indicating that the new inert coated titanium anode prepared by this method has good catalytic active sites. Comparative Example 1 has no catalytic coating on the surface, and the number of catalytic active sites on the anode surface is significantly less than that of the coated embodiment. In addition, the coated new inert titanium anode (Examples 1-6) has a lower oxygen evolution overpotential and a high current efficiency. Because of the coating protection, the corrosion resistance is better; the uncoated anode (Comparative Example 1) has a relatively high oxygen evolution overpotential, which will lead to a lower current efficiency. Because the surface is not protected by the coating, an oxide film has been formed on the surface of the titanium plate, reducing the conductivity and shortening the service life. From the comparison of Examples 1-4, it can be seen that the catalytic performance of the coated anode is mainly affected by the quality of the active substance, the electroplating process and the heat treatment process. Adjusting the electroplating process can significantly change the amount of metal oxide in the coating layer, and the coating quality can directly affect the catalytic activity and life of the anode. The more coating is applied, the longer the life of the anode. IrO2 can significantly reduce the overall oxygen evolution potential of the anode.
[0111] The experimental results of the enhanced life test of the titanium anode of Examples 1-6 and Comparative Examples 1-4 are shown in Figure 3 ,Depend on Figure 3 It can be seen that the life of the anode prepared in the embodiment of the present invention is significantly higher than that of the uncoated titanium anode (Comparative Example 1). Combined with the coating composition table in Table 1, it can be inferred that increasing the content of Ru and Ir can significantly improve the catalytic performance of the anode, and increasing the content of Sn and Ru helps to enhance the stability of the electrode coating and improve the overall performance of the electrode. By comparing Examples 1, 5, 6 and Comparative Example 1, it can be seen that the surface process of the titanium substrate mainly affects the service life of the coating. The appropriate roughness of the titanium substrate surface can significantly increase the surface area of the titanium substrate, increase the bonding degree between the coating and the titanium substrate, and improve the stability, but excessive acid etching will lead to the opposite result. The coating electrodeposition process is affected by temperature, current density, and time, and directly affects the metal oxide composition in the coating. It can be seen from the comparative analysis of the test results of Comparative Examples 1, 2, 3, 4 and Examples 2, 3, and 4 that the electrodeposition process has a significant effect on the life of the coating. Combined with the analysis in Table 1, it can be judged that the deposition process affects the electrochemical properties and life of the coating anode from the two aspects of the quality of the active components of the coating oxide and the coating structure. Therefore, each process for preparing the coated titanium anode can affect the performance of the coated titanium anode. Overall analysis Figure 3 There is no significant regularity in the influence of each condition on the coating performance. The test results of the coated titanium anode are the result of the combined effect of the process conditions in each section.
[0112] In summary, the novel inert titanium anode prepared by the method according to the embodiment of the present invention has good stability and electrochemical performance.
[0113] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A novel inert titanium anode, comprising a titanium substrate and an anode coating, characterized in that: The anode coating is loaded on the surface of the titanium substrate. The anode coating is a layered structure containing three metal oxides. The inner layer of the anode coating is ruthenium oxide, the middle layer is iridium oxide, and the outer layer is tin oxide.
2. The novel inert titanium anode according to claim 1 is characterized in that: The mass ratio of ruthenium oxide, iridium oxide and tin oxide in the anode coating is (0.6-1.2):(0.3-0.7):(0.01-0.05).
3. A method for preparing the novel inert titanium anode according to any one of claims 1 to 2, characterized in that: Ruthenium and iridium are deposited on the surface of a titanium plate in sequence by electrodeposition, a tin-containing solution is then sprayed on the surface by a spraying process, and finally a layered structure coating containing ruthenium, iridium and tin oxides is generated in situ on the surface of the titanium plate by thermal decomposition to obtain the novel inert titanium anode.
4. The method for preparing the novel inert titanium anode according to claim 3, characterized in that: The specific steps include: (1) A titanium substrate is obtained by pretreatment, the titanium substrate is used as a cathode, a metal platinum sheet is used as an anode, and the titanium substrate is immersed in a ruthenium-containing solution, and ruthenium is electrodeposited on the surface of the titanium plate by an electrodeposition method to prepare an electrode A; (2) using the electrode A obtained in step (1) as a cathode and a metal platinum sheet as an anode, immersing the electrodes in an iridium-containing solution, and electrodepositing iridium on the surface of the electrode A by an electrodeposition method to prepare an electrode B; (3) Spraying a tin-containing solution on the surface of the electrode B obtained in step (2), followed by drying and heat treatment to obtain the novel inert titanium anode.
5. The method for preparing the novel inert titanium anode according to claim 4, characterized in that: In step (1), the ruthenium-containing solution comprises RuCl3 at a concentration of 10-15 g / L and NH2SO3H at a pH of 1-2; and / or The solution temperature of the electrodeposition method is 45-50°C and the current density is 1.0-1.5A / dm 2 , the deposition time is 1-2h.
6. The method for preparing the novel inert titanium anode according to claim 4, characterized in that: In step (2), the iridium-containing solution comprises H2IrCl5·6H2O at a concentration of 10-15 g / L and CH3COOH at a concentration of 0.01-0.02 mol / L, and a pH of 4-5; and / or The solution temperature of the electrodeposition method is 85°C and the current density is 1.0-2.0A / dm 2 , the deposition time is 1-2h.
7. The method for preparing the novel inert titanium anode according to claim 4, characterized in that: In step (3), the tin-containing solution is a SnCl4 solution with a concentration of 20 g / L; and / or The drying is infrared drying; and / or The heat treatment temperature is 450-550° C. and the time is 1 hour.
8. The method for preparing the novel inert titanium anode according to claim 3, characterized in that: In step (1), the titanium plate pretreatment specifically includes the following steps: The titanium plate is polished and then immersed in an alkaline solution, washed and then immersed in an oxalic acid solution, washed further, then immersed in anhydrous ethanol for ultrasonic treatment, and washed again to obtain a titanium matrix.
9. The method for preparing the novel inert titanium anode according to claim 8, characterized in that: The alkaline solution is a sodium hydroxide solution or a sodium carbonate solution with a concentration of 5 wt%; and / or The concentration of the oxalic acid solution is 10-15 wt %.
10. The method for preparing the novel inert titanium anode according to claim 8, characterized in that: The ultrasonic treatment time is 10-15 min, and the ultrasonic frequency is 20-30 kHz.
Citation Information
Patent Citations
Preparation method of ruthenium-iridium-tin-titanium coating titanium anode
CN118461064A
Coating titanium anode
CN101235513A
Preparation method of titanium anode
CN102677092A
Iridium composite coating titanium anode and preparation method thereof
CN118932445A
Electrode for electrolysis
JP2008050675A